A educação ambiental como instrumento de gestão ambiental empresarial - Brito, Marcelene Nascimento (2015)
This paper is about Environmental Education in Brazilian Companies (EAEB). The purpose of this work was to analyze, through a literature review, the conceptions and practices of Environmental Education (EA) developed in a business context, as an environmental management tool in order to identify its characteristics and verify its alignment to the concepts of Environmental Education for Sustainable Societies (EASS) which is present in the National Program of Environmental Education (ProNEA). The EAEB is potentially an important tool for environmental management, however, it is facing the challenge of overcoming a reductionism with which it is addressed. In order to achieve this goal, it is essential that the actions and practices are planned and implemented on solid and coherent conceptual bases. With intent of conducting a conceptual analysis, an evaluative study of an environmental education program, with public access, was selected to check its correspondence to the assumptions of the Treatise on Environmental Education for Sustainable Societies and Global Responsibility (TEASS), assumed by ProNEA. By analyzing the results, it was possible to demonstrate that even if a program is considered effective within its proposal, it lacks conceptual improvement to assure that the EA conducted is in accordance to determinations made by ProNEA and that it contemplates the dimension of building Sustainable Societies.